Feedstock Security Analysis for Wood Pellet Production in Thailand - Piyarath Saosee; Boonrod Sajjakulnukit; Shabbir H. Gheewala (Energies, 2020)
Thailand is one of the upcoming wood pellet exporters in the Southeast Asia region. Wood pellet production has been gradually increasing in Thailand; however, the recent trend is more rapid. Therefore, the objective of this study is to analyze the feedstock security for wood pellet production in Thailand. The important issue of feedstock security analysis relates to availability and diversity of feedstock (Shannon index) to meet the increased demand for the wood pellets in the future. The results present that the feedstock supply (from waste wood and fast-growing tree wood) in Thailand is 5.32 million tonnes of wood pellets per year. However, increasing 25% of wood pellet export and 50% of wood pellet domestic use causes a deficit in fast-growing tree wood because para-rubber waste wood is not distributed uniformly in all regions of the country. The present diversity of feedstock supply is quite low (Shannon index 0.17). Increasing the fast-growing tree plantation area in the wastelands could help increase diversity. Recommendations on policy from this study focus on encouragement for the increase in domestic use of wood pellets, cultivation of fast-growing trees in wasteland and optimized logistics management.